Ant assemblage composition explains high predation pressure on artificial caterpillars during early night. (10th December 2019) - Liu, Xiang; Wang, Zhenghong; Huang, Chenyu; Li, Manru; Bibi, Farkhanda; Zhou, Shurong; Nakamura, Akihiro
Abstract : 1. Predator–prey interactions, especially those involving herbivorous insects, are of great importance in maintaining biodiversity. Predation pressure varies temporally in response to prey availability and activity. However, little is known about the patterns and drivers of fluctuations in predation pressure at fine temporal scales. 2. Artificial caterpillars (placed on plant leaves at breast height) were used to assess changes in predation pressure across four time intervals of the day in a monsoonal tropical rainforest in south‐west China. The study examined how assemblage composition of arboreal ants, the dominant predators, changed across the same time intervals. The potential linkages between biotic (arboreal ants) and abiotic (temperature and light intensity) factors with predation rate were evaluated. 3. Predation rate on caterpillars during the early part of the night (19.00–01.00 hours) was significantly higher than in the morning, afternoon, or late night. Ant assemblage composition, rather than species richness or total abundance, best explained the variations in predation rate on artificial caterpillars. 4. The results help to strengthen understanding of trophic interactions by demonstrating that predation pressure fluctuates at finer timescales than previously tested, and that a particular set of ant species may play major roles in predation on caterpillars and possibly other organisms. Abstract : Artificial caterpillars were used to assess changes in predation rate across four temporal intervals per day and evaluated the potential linkages between primary predators (arboreal ants) and predation rate. Predation rate peaked early in the night (19.00–01.00 hours), and was best explained by ant assemblage composition, rather than ant species richness or total abundance per se . The predation pressure fluctuates at finer timescales than previously tested, and that particular set of ant species may play a major role in predation.